Digital Readiness and Sustainable Digital Finance Adoption among MSMEs in Mebidang: The Role of Business Innovation Orientation - Anggi Pratiwi Sitorus; Salman Munthe; Muammar Rinaldi; Rossy Pratiwy Sihombing (Indonesian Journal Economic Review (IJER), 2026)
Digital readiness determines the ability of micro, small, and medium enterprises (MSMEs) to convert access to digital financial services into sustained business value. This study analyzes the effects of digital literacy, digital infrastructure readiness, and security and privacy awareness on sustainable digital finance adoption (SDFA), as well as the subsequent impact of SDFA on business innovation orientation (BIO) among MSMEs in Mebidang, North Sumatra. Survey data from 320 MSME owners or managers in Medan, Binjai, and Deli Serdang were analyzed using partial least squares structural equation modeling with 5,000 bootstrap subsamples. The results indicate that digital literacy (β = 0.312, p < 0.001), digital infrastructure readiness (β = 0.374, p < 0.001), and security and privacy awareness (β = 0.246, p < 0.001) positively influence SDFA. Digital infrastructure readiness is identified as the strongest antecedent. SDFA significantly impacts BIO (β = 0.681, p < 0.001). The model explains 64.2% of the variance in SDFA and 46.4% of the variance in BIO. This study distinguishes sustainable adoption from sporadic digital finance usage by emphasizing continuity, efficiency, transparency, trust, recordkeeping, and responsible financial behavior. The findings suggest that regional MSME programs should integrate infrastructure support, practical digital literacy, cybersecurity capabilities, and the integration of digital finance with bookkeeping and business decision-making.